Maintaining long-term frequent tea consumption could reduce the risk of cognitive decline: results from a 10-year longitudinal study - Huang, Jie; Wang, Hongfen; Wang, Yuying; Xu, Jiaqi; Ni, Jiameng; Li, Mengjie; Chen, Bin; Tang, Zaixiang; Zhang, Yu; Tan, Liping (Frontiers in Nutrition, 2025)
BackgroundPrevious studies have suggested that tea may have neuroprotective effect. This study aimed to investigate the association between tea consumption frequency and cognitive decline, taking into account changes in consumption habits and selection bias.MethodsThis study used data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) in 2008, 2011, 2014, and 2018 years. Changes in tea consumption habits were identified based on the frequency and consistency of tea consumption at baseline and at the last follow-up. Cognitive function was assessed by using Mini-Mental State Examination (MMSE). Cox proportional hazards models were conducted to estimate association between tea consumption habits and cognitive decline. Inverse probability of treatment weighting (IPTW) was applied to reduce selection bias.ResultsConsistently frequent tea consumption reduced the risk of cognitive decline, whereas inconsistently frequent tea consumption did not. Compared with consistently infrequent tea drinkers, the multivariable-adjusted HR of cognitive decline was 0.98 (95% CI: 0.90, 1.06) for inconsistently frequent tea drinkers, and 0.86 (95% CI: 0.76, 0.96) for consistently frequent tea drinkers. With increasing frequency of tea consumption, the risk of developing cognitive decline decreased (P for trend: 0.023). Similarly, the association remained robust after IPTW adjustment. Consistently frequent tea drinkers had a 12% (HR:0.88, 95% CI: 0.77, 0.99) reduced risk of cognitive decline, whereas no significant association was observed for inconsistently frequent tea consumption (HR:0.98, 95% CI:0.91, 1.07) (P for trend < 0.001). Additionally, frequent consumption of both tea and fruit has a synergistic effect on cognitive health (P for interaction = 0.041).ConclusionMaintaining an uninterrupted habit of frequent tea consumption over time could reduce the risk of cognitive decline, whereas inconsistently frequent tea consumption was not significant, even after IPTW adjustment. Regular consumption of tea and fruit has a synergistic effect on cognitive health.